2001
DOI: 10.1289/ehp.011091275
|View full text |Cite
|
Sign up to set email alerts
|

The effects of PCB exposure and fish consumption on endogenous hormones.

Abstract: Previous studies have suggested that exposure to polychlorinated biphenyls (PCBs) may alter thyroid function, but data on effects of PCB exposure on other endogenous hormones has been lacking. The current study is ancillary to a larger investigation of the effects of Great Lakes fish consumption on PCBs and reproductive function. In the current study we examine associations of PCBs, 1,1-bis (4-chlorophenyl)-2,2-dichloroethene (DDE), and fish consumption with thyroid and steroid hormones in 178 men and PCBs, DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
85
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(98 citation statements)
references
References 43 publications
9
85
4
Order By: Relevance
“…Inconsistent with our findings were results from two other human studies that found no associations between p,p′-DDE and thyroid hormones in adult men (Hagmar et al 2001a;Persky et al 2001). Also inconsistent with our results but consistent with what they reported for HCB and PCBs, Takser et al (2005) found an inverse association between p,p′-DDE and total T 3 with no associations between p,p′-DDE and free T 4 or TSH in pregnant women.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Inconsistent with our findings were results from two other human studies that found no associations between p,p′-DDE and thyroid hormones in adult men (Hagmar et al 2001a;Persky et al 2001). Also inconsistent with our results but consistent with what they reported for HCB and PCBs, Takser et al (2005) found an inverse association between p,p′-DDE and total T 3 with no associations between p,p′-DDE and free T 4 or TSH in pregnant women.…”
Section: Discussioncontrasting
confidence: 64%
“…Likewise, inverse associations between PCBs and T 3 levels were also previously observed in the wives of Swedish fishermen (Hagmar et al 2001b) and in German schoolchildren (Osius et al 1999), while another study among Dutch women reported an inverse association with T 3 that was also accompanied by an inverse association with T 4 and a positive association with TSH (Sala et al 2001). Other studies have reported an inverse association between PCBs, and T 4 and/or a positive association between PCBs and TSH, with no association between PCBs and total T 3 (Schell et al 2004;Hagmar 2003;Persky et al 2001;Emmett et al 1988), while another reported no associations between PCBs and thyroid hormones among 160 neonates from North Carolina from 1978 to 1982 (Longnecker et al 2000).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Polychlorinated biphenyls (PCBs) have been linked to a broad range of adverse health effects in humans, from developing fetuses to aging adults (Fein et al 1984;Hicks 1996;Lai et al 2001;Persky et al 2001;Rylander et al 1998;Sauer et al 1994;Schantz et al 1996;Yu et al 1991). However, efforts to ascertain historical PCB exposure and determine a causal relationship with health outcomes such as cancer and immune dysfunction have yielded inconsistent results (Hansen 1998;Kimbrough 1995;Wolff and Toniolo 1995).…”
mentioning
confidence: 99%